Ripe banana peel extract: a natural protector of testicular health in experimental models - Ezeagu, Darlington Kenechukwu; Ofoego, Uzozie Chikere (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Spermatogenesis is highly vulnerable to oxidative stress, which can be intensified by environmental toxins like paraquat (PQ), an herbicide known for its potent toxicity, particularly in inducing reactive oxygen species (ROS). Musa sapientum (banana), has garnered attention for its antioxidant properties, particularly in its peel, which contains bioactive compounds such as flavonoids and phenols. This study investigated the protective effects of the ethanolic extract of ripe banana peel on male reproductive health in Wistar rats exposed to paraquat-induced testicular dysfunction. Methods: After acclimatization and toxicity tests, 25 rats were divided into 5 groups. Group A served as the control, receiving rat feed and distilled water. Group B received 20mg/kg of paraquat. Group C received 1000mg/kg of ethanolic banana peel extract. Groups D and E both received 20mg/kg of paraquat followed by 500mg/kg and 1000mg/kg of banana peel extract respectively for three weeks. Sperm quality and testicular histoarchitecture were assessed, with semen samples collected from the epididymis and testes processed for histological evaluation. Results: Paraquat exposure significantly reduced sperm motility, count, and testicular weight, while increasing sperm abnormalities and histological damage. These effects were likely due to ROS-induced lipid peroxidation and DNA fragmentation. Treatment with banana peel extract significantly improved sperm motility, count, and testicular histoarchitecture, indicating its antioxidant properties. Conclusions: This study suggests that banana peel extract has potent antioxidant effects and could alleviate paraquat-induced male infertility.